2024
DOI: 10.1021/acsnano.3c08662
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reaction-Generated Aldehyde-Scavenging Polypeptides-Curcumin Conjugate Nanoassemblies for Combined Treatment of Spinal Cord Injury

Yixuan Liu,
Feng Lin,
Cheng Wu
et al.

Abstract: The microenvironment after traumatic spinal cord injury (SCI) involves complex pathological processes, including elevated oxidative stress, accumulated reactive aldehydes from lipid peroxidation, excessive immune cell infiltration, etc. Unfortunately, most of current neuroprotection therapies cannot cope with the intricate pathophysiology of SCI, leading to scant treatment efficacies. Here, we developed a facile in situ reaction-induced self-assembly method to prepare aldehyde-scavenging polypeptides (PAH)-cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A study by Yuan et al utilized epigallocatechin gallate (EGCG) nanoparticles to effectively suppress the inflammatory response and mitigate ROS, thereby exerting a neuroprotective effect . Similarly, Liu et al prepared aldehyde-scavenging polypeptides (PAH)-curcumin conjugate nanoassemblies (named PFCN), which released curcumin and PAH under acidic and oxidative microenvironmental conditions, thereby achieving the clearance of inflammatory factors, ROS, and aldehydes, providing synergistic multifactorial regulation for SCI repair . Zhu et al constructed high deferoxamine loading nanoparticles, and demonstrated excellent scavenging performance in iron-overloaded cell model and energetically exhibited neural cell protection …”
Section: Discussionmentioning
confidence: 99%
“…A study by Yuan et al utilized epigallocatechin gallate (EGCG) nanoparticles to effectively suppress the inflammatory response and mitigate ROS, thereby exerting a neuroprotective effect . Similarly, Liu et al prepared aldehyde-scavenging polypeptides (PAH)-curcumin conjugate nanoassemblies (named PFCN), which released curcumin and PAH under acidic and oxidative microenvironmental conditions, thereby achieving the clearance of inflammatory factors, ROS, and aldehydes, providing synergistic multifactorial regulation for SCI repair . Zhu et al constructed high deferoxamine loading nanoparticles, and demonstrated excellent scavenging performance in iron-overloaded cell model and energetically exhibited neural cell protection …”
Section: Discussionmentioning
confidence: 99%